External fixation can be an option for proximal humerus fractures Neer 3-4 - Maluta, Tommaso; Amarossi, Andrea; Dorigotti, Andrea; Bagnis, Francesco; Samaila, Elena Manuela; De Luca, Lapo; Pezze, Lorenzo; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2020)
Background: Proximal humeral fractures (PHF) account for 4-6% of all fractures and 25% of humeral fractures. While conservative treatment is the gold standard for simple fractures, there is no consensus about the best treatment choice for complex PHF in the elderly.Recently a new external fixator was introduced in clinical practice for treatment of complex PHF.  Aim of the study was to evaluate the functional results of this therapeutic approach.Methods: Data were retrospectively analyzed. Inclusion criteria were: three- and four- parts PHF according to Neer, treatment with closed reduction and external fixation, normal Abbreviated Mini Mental Test score, independence in the daily living, non-pathological fracture, glenohumeral joint with moderate osteoarthritic changes and availability of clinical and radiological follow-up. For each patient demographic data, comorbidities, surgery time and estimated blood loss were recorded. Clinical and radiological evaluation were performed at 1, 2, 6, 12 months.Results: 17 patients were enrolled. Mean age was 69.7 years. Fractures were classified according to Neer as type III in 10 cases and type IV in 7 cases. The mean operating time was 22 minutes. Mean Constant score value at follow up was 74 ±11,52 at 2 months, 82 ± 11,16 at 6 months and 85 ± 9,86 at 12 months.Conclusion: These preliminary results show that the studied system is easy to use, minimally invasive, effective in reducing surgical and hospitalization time. The results in terms of functional recovery are encouraging, showing a reduced number of complications.